2012
DOI: 10.1039/c2cc30233k
|View full text |Cite
|
Sign up to set email alerts
|

“Inverse” synthesis of polymer bioconjugates using soluble supports

Abstract: Well-defined cleavable or non-cleavable soluble polystyrene supports were prepared by atom transfer radical polymerization and utilized for the iterative synthesis of functional hexapeptides. This approach allowed rapid and efficient liquid phase synthesis of peptide-polymer conjugates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…Telechelic oligoamides were obtained after three amidification and two copper‐assisted alkyne‐azide cycloaddition reactions followed by cleavage with a mixture of trifluoroacetic acid and dichloromethane (TFA/DCM = 9/1). Contrary to our previous work, we were interested in using an unmodified Wang resin, strategy that will induce obtaining the targeted oligomers without any residual linker present on the oligomer …”
Section: Resultsmentioning
confidence: 99%
“…Telechelic oligoamides were obtained after three amidification and two copper‐assisted alkyne‐azide cycloaddition reactions followed by cleavage with a mixture of trifluoroacetic acid and dichloromethane (TFA/DCM = 9/1). Contrary to our previous work, we were interested in using an unmodified Wang resin, strategy that will induce obtaining the targeted oligomers without any residual linker present on the oligomer …”
Section: Resultsmentioning
confidence: 99%
“…Colonies of infected E. coli bacteria are grown and for six of these colonies the DNA was sequenced, all yielded identical amino-acid sequences: NHWSDKRAQITI. Peptides (AD, short for adhesion domain) and peptide-polymer (PEO-AD) conjugates (with a PEO block, M n = 3.2·10 3 g/mol) with this sequence were synthesized by solid-phase peptide synthesis using inverse conjugation strategies (60). Additionally, a fluorescent marker (carboxyfluorescein, abbreviated fam) and a spacer (two glycine residues) were incorporated, yielding fam-GG-NHWSDKRAQITI.…”
Section: Phage Display Assisted Design Of Bioconjugatesmentioning
confidence: 99%
“…In a series of recent publications, we have shown that atom‐transfer radical polymerization (ATRP) is a very convenient method for preparing tailor‐made soluble polymer supports. ATRP is a controlled radical‐polymerization technique that permits fine control of the molecular structure of synthetic polymers .…”
Section: Introductionmentioning
confidence: 99%